Psychopathology and Somatic Complaints: A Cross-Sectional Study with Portuguese Adults - Becker, Joana Proença (2021)
(1) Background: Functional somatic symptoms (FSS) are physical symptoms that cannot be fully explained by medical diagnosis, injuries, and medication intake. More than the presence of unexplained symptoms, this condition is associated with functional disabilities, psychological distress, increased use of health services, and it has been linked to depressive and anxiety disorders. Recognizing the difficulty of diagnosing individuals with FSS and the impact on public health systems, this study aimed to verify the concomitant incidence of psychopathological symptoms and FSS in Portugal. (2) Methods: For this purpose, 93 psychosomatic outpatients (91.4% women with a mean age of 53.9 years old) and 101 subjects from the general population (74.3% women with 37.8 years old) were evaluated. The survey questionnaire included the 15-item Patient Health Questionnaire, the 20-Item Short Form Survey, the Brief Symptom Inventory, the Depression, Anxiety and Stress Scale, and questions on sociodemographic and clinical characteristics. (3) Results: Increases in FSS severity were correlated with higher rates of depression, anxiety, and stress symptoms. The findings also suggest that increased rates of FSS are associated with lower educational level and female gender. (4) Conclusion: Being aware of the relationship between FSS and psychopathological symptoms and the need to explore psychosocial issues during clinical interviews may favor early detection of these cases. The early detection of mental disorders is essential for individuals' adherence to treatments, reflecting on healthcare costs.